STUDYING THE EFFECT OF VITAMIN D AND CALCIUM PREPARATIONS IN THE TREATMENT OF OSTEOPOROSIS AFTER GLUCOCORTICOSTEROID THERAPY IN RHEUMATOID ARTHRITIS (World Bulletin of Public Health, 2025)
This article discusses methods for preventing osteoporosis after glucocorticosteroid therapy in rheumatoid arthritis, the results of scientific studies, recommended methods, and directions.